At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

4Evaluate the expression.g(h + 2h) use g = 2 and h = 6

Sagot :

The given expression is

g(h + 2h)

We woulld substitute g = 2 and h = 6 into the given expression. It becomes

2(6 + 2 * 6)

= 2(6 + 12)

= 2(18)

= 36